The calorie counter-intuitive effect of restaurant menu calorie labelling - McGeown, Laura (Can J Public Health, 2019)
As of January 1, 2017, the Healthy Menu Choices Act mandates that food service premises with 20 or more locations in Ontario must display the number of calories in every food item sold on menus. The impetus for this legislation was to enable Ontarians to become aware of the calorie content of foods and beverages consumed outside the home, and make healthier dietary choices while dining out. Though arising as an initiative to attenuate the development of obesity and current obesity rates, evidence suggests menu labelling does not significantly alter individuals’ food choices. Moreover, focusing primarily on caloric content may be an ineffective, and perhaps detrimental, strategy to effect change in the obesity epidemic. Beyond the initiative’s questionable utility, there has been a lack of consideration as of yet to the unintended negative implications this initiative may have on eating disorder (ED) symptomatology in the general population and those attempting to recover from an ED. The objective of the current commentary is thus to argue that in light of evidence of minimal benefit and the potential for harm, nutrition labelling on menus may be a misguided public health initiative.